Tuberculose genital: uma causa rara de hemorragia pós-menopausa - Júlio, Catarina (2017)
BACKGROUND Tuberculosis remains a global health problem, being the genitourinary tract the second most common site for tuberculosis infection after the lungs. Genital tuberculosis is now undergoing a worrying recrudescence. CASE REPORT We report two cases of postmenopausal women who presented with vaginal bleeding. General physical and gynecological examination detected no abnormality. Transvaginal pelvic ultrasound showed fluid in the endometrial cavity in both cases. The office hysteroscopy was suggestive of focal endometrial thickness and an endometrial biopsy was performed. The histopathologic examination of biopsies found epithelioid cell granulomas without malignant cells. Culture of the endometrium was positive for Mycobacterium tuberculosis. Involvement of other systems was not detected. The patients started receiving antituberculosis treatment. CONCLUSION Genital tuberculosis is rare in postmenopausal women and responsible for only approximately 1% of postmenopausal bleeding. However it is a curable disease and an early diagnosis is important and may prevent unnecessary invasive procedures for the patient.